Methamphetamine dependence in Malaysia: psychiatric co-morbidity and suicidality, methamphetamine induced psychosis, genetic polymorphisms and efficacy of aripiprazole in the treatment of methamphetamine dependence / Ahmad Hatim Sulaiman - Ahmad Hatim, Sulaiman (2011)
Methamphetamine dependence remains a worldwide problem and Malaysia is no exception. The widespread of methamphetamine dependent has given an impact that can be felt at various levels, from the individual, to the individual’s family, community and society. Unfortunately, there are not many studies done on the issues of methamphetamine dependence in Malaysia. We are still lacking in published data especially in terms of prevalence, psychiatry morbidity, genetic risk factors and treatment aspect. Based on the result of the study, we found that the prevalence of psychiatric co-morbidity was 54.4% and the prevalence of suicidality was 12.1 %. The subjects had high rates for methamphetamine-induced psychosis with 47.9% had at least one episode of psychotic symptoms and 13.0% were still having psychotic symptoms at the time of assessment. Our results showed that the distribution of the BDNF Val66Met genotype in Chinese subjects with methamphetamine dependence and methamphetamine psychosis were significant compared with controls. The frequency of the 66Val allele in methamphetamine-dependent subjects was higher than that in the control group, suggesting that the 66Val carriers are more susceptible to methamphetamine dependence. However, 66Val allele frequency in other ethnicities was not significantly different from the controls. Among those who were having methamphetamine-induced psychosis, treatment with aripiprazole was associated with significant decline in the Positive And Negative Symptoms Scale (PANSS) and Clinical Global Impression of Severity (CGI-S) score. Aripiprazole was generally well tolerated with no serious adverse event occur. In the randomised controlled trial study, 84.2% of participants randomized to aripiprazole completed the study compared to only 50% of the placebo group completed. There was a statistically significant difference between groups in the amount of time spent in treatment, with those given aripiprazole retained for an average of 48.7 days (+ 4.0) compared with only 37.1 days (+ 5.0) for the placebo group. The survival curves results showed that participants in the aripiprazole group were less likely to drop out of the study than those in the placebo group. The difference was statistically significant. Psychotic symptoms as measured by PANSS and CGI were decreased among participants who were randomized to aripiprazole treatment but those who were randomized to placebo showed an increased in the total PANSS and CGI score. However there were no statistically significant effects for aripiprazole relative to placebo on methamphetamine use verified by urine drug screen. Aripiprazole treatment was not associated with any serious adverse event. Based on the findings: - Support the fact that methamphetamine users are a high-risk population for psychosis. - Suggest that the BDNF Val66Met polymorphism may contribute to methamphetamine dependence and psychosis in the Chinese population but not in other Malaysian ethnicities. - Suggest that aripiprazole was efficacious and safe options for the treatment of methamphetamine-induced psychosis. - Aripiprazole was no more effective than placebo in maintaining abstinence from methamphetamine use. However, it facilitated treatment retention and reduced the occurrence of psychotic symptoms in patients with methamphetamine dependence.